Analisis Putusan Hakim Dalam Perkara Hak Asuh Anak Yang Belum Mumayyiz Pasca Perceraian - Ramadhani, Dwi Aryanti; Abdullah, Nayla Putri; Yadila, Natasya; Amelia, Sabina Putri; Widiastiwi, Alisha Reva; Hermawati, Mutiara; Harsanti, Khairunnisa Putri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Child custody is one of the consequences that arise after divorce. This is because parents still have an obligation to provide maintenance and protection for the growth and development of children. In this study the author focuses on analyzing the judge's decision in the case of custody of children who have not been able to distinguish good and bad rights independently (mumayyiz) after divorce. This research is aimed at understanding the legal considerations and factors that influence the judge's decision in determining the custody of children who have not reached the age of mumayyiz. The research method used is the normative juridical method with a statutory approach and a case approach by analyzing relevant court decisions. The results of this study indicate that in making decisions judges consider psychological factors and factors of the child's interests in supporting his growth and development. These considerations are based on the facts and evidence presented during the trial. This research recommends the need for clearer and more consistent guidelines in child custody decisions to ensure optimal protection for children involved in divorce cases.